Viral Gastroenteritis: Clinical Manifestations, Nursing Care Strategies, and Health Data Perspectives - Hamami, Reham Hussain; Hanshali, Jawaher Ali Makey; Almanbahi, Walaa Mohammed; Alenezi, Farhah Falah Srayan; Almutairi, Amani Mazyad; Almotiab, Mona Abdulaziz R; Alhalawi, Nada Mosa; Amri, Faisal Mohammed Ali; Al-Mutairi, Faisal Lafi; Amri, Eman Mohammed Ali; Al-Rashidi, Manal Zaal Amesh; Aldosery, Abdallah Saad Said; et al. (Saudi Journal of Medicine and Public Health, 2025)
<span style="font-size: 11pt; font-family: Aptos; background-color: transparent; font-weight: bold; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; vertical-align: baseline; white-space-collapse: preserve;">Background:<span style="font-size: 11pt; font-family: Aptos; background-color: transparent; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; vertical-align: baseline; white-space-collapse: preserve;"> Viral gastroenteritis, commonly known as the "stomach flu," is a highly contagious infection causing inflammation of the stomach and intestines. It is a major global health concern, leading to significant morbidity, healthcare burdens, and economic costs, with norovirus and rotavirus being the most prevalent pathogens. <span style="font-size: 11pt; font-family: Aptos; background-color: transparent; font-weight: bold; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; vertical-align: baseline; white-space-collapse: preserve;">Aim:<span style="font-size: 11pt; font-family: Aptos; background-color: transparent; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; vertical-align: baseline; white-space-collapse: preserve;"> This article aims to provide a comprehensive overview of viral gastroenteritis by synthesizing its clinical manifestations, outlining evidence-based nursing care strategies, and exploring the role of health data analytics in improving prevention, outbreak management, and public health surveillance. <span style="font-size: 11pt; font-family: Aptos; background-color: transparent; font-weight: bold; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; vertical-align: baseline; white-space-collapse: preserve;">Methods:<span style="font-size: 11pt; font-family: Aptos; background-color: transparent; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; vertical-align: baseline; white-space-collapse: preserve;"> The review synthesizes current clinical guidelines and best practices. It details the diagnostic approach, which is primarily based on clinical presentation and symptom assessment, with laboratory confirmation reserved for severe or outbreak scenarios. Nursing interventions are framed within a patient-centered model, focusing on thorough assessment, hydration management, and education. <span style="font-size: 11pt; font-family: Aptos; background-color: transparent; font-weight: bold; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; vertical-align: baseline; white-space-collapse: preserve;">Results:<span style="font-size: 11pt; font-family: Aptos; background-color: transparent; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; vertical-align: baseline; white-space-collapse: preserve;"> The primary clinical manifestations include acute onset of watery diarrhea, vomiting, abdominal cramps, and nausea, which can lead to dehydration and electrolyte imbalances, particularly in vulnerable populations. Effective management is centered on vigorous oral or intravenous rehydration. Results highlight that meticulous nursing care—encompassing fluid balance monitoring, symptom control, and strict infection prevention protocols—is critical to patient recovery and containing transmission. Furthermore, leveraging health data enables real-time outbreak detection and informs targeted public health interventions. <span style="font-size: 11pt; font-family: Aptos; background-color: transparent; font-weight: bold; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; vertical-align: baseline; white-space-collapse: preserve;">Conclusion:<span style="font-size: 11pt; font-family: Aptos; background-color: transparent; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; vertical-align: baseline; white-space-collapse: preserve;"> A multifaceted approach combining prompt clinical management, diligent nursing care, and robust health data systems is essential for reducing the impact of viral gastroenteritis.